Filament winding technique: SWOT analysis and applied favorable factors - Ma, Quanjin; Rejab, M. R. M.; Idris, Mat Sahat; Zhang, Bo; Manoj Kumar, Nallapaneni (SCIREA, 2019)
Filament winding technique is an automated composite fabrication technique, which is mainly used to produce tubular structure such as storage tanks, vessels, missiles and rocket motor cases. In recent 20 years, filament winding technique has developed as a mature fabrication technology, which is depended on various applied factors. Filament wound composite product applied fields are also influenced by different favourable factors. In this paper, a proper analysis method is carried out applied factors, which can enhance filament winding technique usage rate. Primarily, SWOT (Strength, Weakness, Opportunity, and Threat) analysis of filament winding technique is fully analysed. Secondly, all the applied favourable factors were classified and discussed under six categories, which relates the Wind Energy, Building & Construction, Mass Transportation, Chemical/Corrosion, Infrastructure, and Militray & Defense. Finally, applied favourable factors were discussed in details, and conclusion were summarized and highlighted, which can advance filament winding technique and increase filament wound composite product applied fields.